Standardization of fluorescence molecular imaging systems - Gorpas, Dimitris; Koch, Maximilian; Anastasopoulou, Maria; Klemm, Uwe; Ntziachristos, Vasilis (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2017)
Lack of standardization in fluorescence imaging challenges its clinical translation. We investigate the use of a composite phantom to perform standardization, which could serve as a framework toward the benchmarking of fluorescence imaging systems.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Fluorescence molecular imaging; Imaging systems benchmarking; Standardization